2011
DOI: 10.1101/cshperspect.a006395
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Nonamyloid/Tau Based Pharmacologic Treatment for Alzheimer Disease

Abstract: In this work we consider marketed drugs for Alzheimer disease (AD) including acetylcholinesterase inhibitors (AChE-Is) and antiglutamatergic treatment involving the N-methyl-D-aspartate (NMDA) receptor. We discuss medications and substances available for use as cognitive enhancers that are not approved for AD or cognitive impairment, and other neurotransmitter-related therapies in development or currently being researched. We also review putative therapies that aim to slow disease progression by mechanisms not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 99 publications
(90 reference statements)
1
40
0
1
Order By: Relevance
“…Current treatments are palliative at best and newer therapies remain unproven. Knowing who is a risk and why will make prevention and management easier in the future (Aisen et al 2011; Lee et al 2011; Schenk et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Current treatments are palliative at best and newer therapies remain unproven. Knowing who is a risk and why will make prevention and management easier in the future (Aisen et al 2011; Lee et al 2011; Schenk et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The current treatments for AD are acetylcholinesterase inhibitor donepezil (Aricept), rivastigmine tartrate (Exelon), galantamine hydrobromide (Razadyne), and noncompetitive antagonist of the N-methyl-D-aspartate (NMDA) receptor memantine hydrochloride (Namenda), which were approved by the Food and Drug Administration in 1996, 1998, 2001, and 2003, respectively (reviewed in [2]). Numerous additional medications and substances have also been investigated, aiming to treat or prevent AD.…”
Section: Introductionmentioning
confidence: 99%
“…A much hoped-for outcome of the intensive therapeutic research reviewed by Schenk et al (2011), Lee et al (2011), andAisen et al (2011) is that at least one of the agents currently in phase 2 or 3 clinical trials will have shown sufficient efficacy and safety to have been approved as the first disease-modifying treatment for AD. However, even if this central goal is only achieved after 2020, it has become apparent that a new diagnostic and therapeutic paradigm is entering the AD field.…”
Section: Clinical Trials and Treatmentmentioning
confidence: 99%